Functional status of acute stroke patients in University Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia - Abd Rahim, Rameezan Begam; Omar, Zaliha (Malaysian Medical Association, 2005)
Stroke is a leading cause of death and disability in most developed countries and developing nations. Majority of the stroke survivors are left with significant physical and cognitive impairments. In addition to the improved acute stroke care, they often benefit from rehabilitation in improving their function. This was the first study done to document function for post stroke patients in Malaysia. It was prospective study conducted to document functional status of acute stroke patients upon admission, discharge and at 3 months post stroke. Assessment of functional status for these patients are based on their activities of daily living and ambulation i.e. self-care, sphincter control, mobility, locomotion, communication and social cognition. It is also aimed to describe their demographic and clinical characteristics. Correlation of functional status at 3 months post stroke with the initial severity of stroke was also explored. A total of fifty-one patients with acute stroke in University Malaya Medical Centre (UMMC) were recruited. The patient's age ranged from 38 to 83 years with a mean of 60.2 years. Thirty-six patients (71%) were first stroke sufferers and fifteen patients (29%) had recurrent stroke. At discharge from acute stay, 13% of patients were able to ambulate with aids and 87% needed assistance for ambulation in varying degrees. Eighty-two percent of patients showed improvement in overall function (both motor and cognition) at 3 months post stroke. Sixty percent of patients were independent in ambulation and 40% required assistance. Significant correlation was seen between the initial severity of stroke and functional status at 3 months post stroke. Functional status of patients with stroke has improved at 3 months post stroke. A comprehensive rehabilitation medicine programme should be incorporated into management of stroke patients to expedite functional recovery and improve patient's independence.